A CFD analysis of air quality and carbon dioxide distribution in a carrycot - Sandra Sif Guðbrandsdóttir 1989- (2024)
The tradition of placing infants outdoors for sleep in Iceland has persisted since the early 1900s, despite limited research on the safety and benefits of outdoor sleeping. This study aims to explore air quality within a carrycot, focusing on the concentration of carbon dioxide, which is a critical factor for infant health. Using Computational Fluid Dynamics (CFD) simulations, two scenarios were analysed: one with natural ventilation (open carrycot shaft) and one without ventilation (closed carrycot shaft). The simulations were conducted using the ANSYS Fluent software, applying the RNG kappa-epsilon turbulence model to capture the dynamics of airflow and carbon dioxide dispersion. Results showed that natural ventilation significantly reduces carbon dioxide levels, maintaining concentrations within safe limits. In contrast, the closed carrycot scenario led to a hazardous accumulation of carbon dioxide, highlighting the importance of efficient ventilation. This study underscores the need for effective ventilation systems in carrycots to ensure a safe sleeping environment for infants. The findings provide information on the design and use of carrycots, with implications for both safety guidelines and future research.